Analisis Tantangan Dan Pendekatan Strategis Dalam Penerapan Kurikulum Merdeka Di SDN 106161 Laut Dendang - Mutia Sari Sinaga; Nahal Dita Siregar; Hanna Syazidah; Nur Rahmi Br. Siagian; Arjuna Rajaguguk; Khairunnisa Khairunnisa (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The implementation of the Merdeka Curriculum at SDN 106161 Laut Dendang faces various challenges that need to be overcome through a strategic approach. This article aims to analyze the challenges faced in implementing the Merdeka Curriculum and identify strategic approaches that can be adopted to overcome these challenges. Data was collected through interviews with teachers and school principals as well as direct observation. The results showed that the main challenges include limited resources, resistance to change, and lack of teacher training. The recommended strategic approach includes increasing teacher capacity, strengthening collaboration between stakeholders, and providing adequate resources.